Legal Settlement for Violations of the Notary Profession as a Land Mafia - Puspitasari, Niken Ayu (Jurnal Daulat Hukum, 2023)
This research discusses the legal settlement of notaries who commit professional violations with the aim of analyzing and explaining the legal settlement process of notaries who violate the law and the impact of deeds that are proven to violate the law as a land mafia. The type of research conducted is normative research or doctrinal research. The result of this research is that the Notary in making the deed must be responsible for the form of the deed, must not deviate from the provisions stipulated in the Notary Position Law. Some common reasons that can cause the cancellation of an agreement: incompetence, invalidity, error, deceit, violence, law or power. The validity of the deed generally depends on if the notary is involved in a violation of the law, the aggrieved party or the authorities can take legal steps to review and cancel or correct the deed made by the Notary.